2012
DOI: 10.1158/1078-0432.ccr-11-0625
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemotherapy with Intensive Consolidation for Primary CNS Lymphoma: A Pilot Study and Prognostic Assessment by Diffusion-Weighted MRI

Abstract: Purpose We evaluated a novel therapy for primary central nervous system (CNS) lymphoma (PCNSL) using induction immunochemotherapy with high-dose methotrexate, temozolomide and rituximab (MT-R) followed by intensive consolidation with infusional etoposide and high-dose cytarabine (EA). In addition, we evaluated the prognostic value of the minimum apparent diffusion coefficient (ADCmin) derived from diffusion-weighted magnetic resonance imaging (DW-MRI) in patients treated with this regimen. Experimental Desig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 43 publications
5
86
2
1
Order By: Relevance
“…Once the diagnosis of PCNSL is confirmed, high‐dose methotrexate should be promptly administered as the first‐choice treatment. In addition, methotrexate in combination with other chemotherapeutic agents,41 autologous stem cell transplantation,42, 43 or rituximab44, 45 have been found to improve prognosis of patients with PCNSL.…”
Section: Discussionmentioning
confidence: 99%
“…Once the diagnosis of PCNSL is confirmed, high‐dose methotrexate should be promptly administered as the first‐choice treatment. In addition, methotrexate in combination with other chemotherapeutic agents,41 autologous stem cell transplantation,42, 43 or rituximab44, 45 have been found to improve prognosis of patients with PCNSL.…”
Section: Discussionmentioning
confidence: 99%
“…Bimbaum et al recently reported the benefits of rituximab in addition to MTX and IFO over MTX and IFO in 36 cases of primary CNS lymphoma in a retrospective analysis [6]. In prospective study, some investigators described promising response rate and survival in primary CNS lymphoma by multi-agent chemotherapy including rituximab as induction therapy [4, 5,7]. Therefore, intravenous administration of rituximab for CNS recurrence in systemic DLBCL may be considered as a treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we did not use rituximab in the study [3]. Recently, regarding primary CNS lymphoma (PCNSL), intravenous rituximab in addition to combined chemotherapy has been accepted as the standard treatment strategy [4][5][6][7]. Furthermore, CNS recurrence of systemic DLBCL is usually premonitory symptom of systemic recurrence, therefore, administration of rituximab in the salvage therapy may be considered as prevention for systemic reoccurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The 2-year OS was 58% when all patients were analyzed and 93% in the cohort of patients who had qualified for and received consolidation therapy with etoposide and cytarabine without evidence of neurotoxicity [45]. This regimen was further evaluated within a multicenter study resulting in survival curves which display evidence of a plateau.…”
Section: Other Approaches For Consolidation Therapymentioning
confidence: 99%